Conversa Brasileira - Kelm, Orlando R. (Open textbook library., 2013)
Conversa Brasileira is an online open access site that contains a series of 35 video scenarios in which Brazilians talk about their daily activities, everything from hobbies to shopping, and from traffic jams to soccer games. These materials are designed to help intermediate- and advanced-level learners of Portuguese to analyze the way that Brazilians really talk and improve in their own proficiency and fluency. This textbook provides a hardcopy of all of the online materials, including the dialog transcriptions, English translations, and lesson notes that link to the original website.